PEMBERDAYAAN EKONOMI MELALUI PENDISTRIBUSIAN ZAKAT IZI (INISIATIF ZAKAT INDONESIA) KOTA PEKANBARU DALAM PENGUATAN EKONOMI PELAKU UMKM (USAHA MIKRO KECIL MENENGAH) - Muhammad Nasri; Sabiruddin; Muhammad Fauzi (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2023)
Abstract. This research is based on the efforts of the Pekanbaru City IZI zakat institution to strengthen the economy of mustahik as MSME actors through the distribution of zakat funds which are directed at the mustahik empowerment program in order to improve the economy and welfare. The aim of this research is to understand the process of distributing zakat funds carried out by IZI in empowering the mustahik economy and IZI Pekanbaru City's efforts to strengthen the economy of MSMEs. This research method is a qualitative approach. The informants for this research were the Head of the Empowerment and Utilization Division, 2 IZI employees and 2 IZI mustahik who work as MSME actors. Data collection techniques are observation, interviews and documentation. The process of analyzing data is data selection, data clarification and data analysis and interpretation. The results of the research show that IZI Pekanbaru City carries out economic empowerment through the distribution of zakat. IZI Pekanbaru City strengthens the economy of MSMEs (Micro Small and Medium Enterprises) by distributing zakat funds by giving or channeling zakat funds to mustahik by collecting data through social media, print media and recommendations from donors or mosques. then the empowerment program is by providing business equipment assistance to mustahik who have special skills in their respective fields.